Intraluminal brachytherapy in oesophageal cancer: defining its role and introducing the technique - Lettmaier, Sebastian; Strnad, Vratislav (Journal of Contemporary Brachytherapy, 2014)
Intraluminal brachytherapy plays an important role in the treatment of oesophageal tumours. This article aims to define this role in the curative as well as in the palliative treatment settings drawing on data from the literature, and also emphasizing its potential for harm when used inexpertly. It also provides a short introduction to practical aspects of the treatment procedure and treatment planning.
EVALuna2:18192